Global methylation levels in peripheral blood leukocyte DNA by LUMA and breast cancer: a case–control study in Japanese women - Kuchiba, A (Nature Publishing Group, 2014)
BACKGROUND: Global hypomethylation has been suggested to cause genomic instability and lead to an increased risk of cancer. We examined the association between the global methylation level of peripheral blood leukocyte DNA and breast cancer among Japanese women. METHODS: We conducted a hospital-based case–control study of 384 patients aged 20–74 years with newly diagnosed, histologically confirmed invasive breast cancer, and 384 matched controls from medical checkup examinees in Nagano, Japan. Global methylation levels in leukocyte DNA were measured by LUminometric Methylation Assay. Odds ratios (ORs) and 95% confidence intervals (CIs) for the associations between global hypomethylation and breast cancer were estimated using a logistic regression model. RESULTS: Compared with women in the highest tertile of global methylation level, ORs for the second and lowest tertiles were 1.87 (95% CI=1.20–2.91) and 2.86 (95% CI=1.85–4.44), respectively. Global methylation levels were significantly lower in cases than controls, regardless of the hormone receptor status of the cancer (all P values for trend <0.05). INTERPRETATION: These findings suggest that the global methylation level of peripheral blood leukocyte DNA is low in patients with breast cancer and may be a potential biomarker for breast cancer risk.